Reduced cooperative behavior as a cost of high testosterone in a lekking passerine bird. (11th December 2019) - Vernasco, Ben J; Horton, Brent M; Moore, Ignacio T; Ryder, T Brandt
Abstract: Many studies have identified the reproductive benefits of cooperative behaviors, yet few have identified the mechanisms that underlie these behaviors. Mechanistic studies can inform our understanding of why some individuals are more or less cooperative, as well as identify the physiological constraints imposed upon the evolution of reproductive traits. Male wire-tailed manakins ( Pipra filicauda ) exhibit cooperative courtship behaviors and more cooperative territory holders have been shown to exhibit higher reproductive success. To begin to understand the proximate basis of cooperative display behaviors, we conducted both an observational study and an experimental study. Because coordinated courtship displays underlie this form of cooperation, our study also examined both the hormonal and social drivers of individual variation in courtship behavior more broadly (e.g., courtship display rates). Our observational study revealed that males with higher testosterone levels performed fewer cooperative display bouts. In addition, our experimental study demonstrated that the proportion of a male's courtship displays that were cooperative decreased after being administered a testosterone-filled hormone implant. We found no relationship between an individual's courtship display effort (i.e., display rate and time spent performing courtship displays) and circulating testosterone in either study. However, more cooperative males spent a greater proportion of time performing courtship displays than did less cooperative males, suggesting that testosterone may indirectly mediate courtship display behaviors by influencing a territory holder's cooperative behavior. Overall, both our observational and experimental results suggest that reduced cooperative behavior is a cost of maintaining high levels of testosterone for territory-holding males. Lay Summary: We show that reduced cooperative behavior is a cost of high testosterone among male wire-tailed manakins. Reduced cooperative behavior is costly because more cooperative males have higher reproductive success. Males that were more cooperative also spent more time displaying. Testosterone was not related to how much time a male spent displaying nor their display rate; however, our results suggest that testosterone may indirectly mediate a male's courtship display effort by acting up their cooperative behavior.